Separation of CH4/N2 of Low Concentrations From Coal Bed Gas by Sodium-Modified Clinoptilolite - Hao, Xiaofei; Li, Zhen; Hu, Hongjie; Liu, Xueqin; Huang, Yanqiu (Frontiers in Chemistry, 2018)
Clinoptilolite is widely natural mineral. It is mainly composed of Al2O3, SiO2 with exchangeable cations such as Ca, K, Mg and Na. In this research, raw clinoptilolite was treated with grinding, gravimetric concentration and ion-exchange using difference concentrations NaCl solutions. Then the modified clinoptilolites powder is prepared into particles as adsorbents between 0.5 and 1.5mm. Then the adsorbents were applied to CH4 separation in coal mine gas. The raw clinoptilolite and modified clinoptilolites using difference concentrations NaCl solutions were obtained, which were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscope, X-ray fluorescence, Fourier transform infrared spectrometer and BET specific surface area. The CH4 absorptivity for raw clinoptilolite and modified clinoptilolites using pressure swing adsorption (PSA) was used to evaluate the CH4 separation ability. It indicated that the ion-exchanged clinoptilolite using 0.2 mol/L NaCl solutions was found to be promising for the kinetic PSA separation of CH4/N2 giving the better absorptivity and influence factors concerning the CH4 separation. Based on the simulated static experiments, it indicated that CH4 and N2 are both capable of diffusing into the clinoptilolites while N2 adsorptions of clinoptilolites are more excellent. The experiment results also indicated that adsorption capability of ion-exchanged clinoptilolite using 0.2 mol/L NaCl solutions was the optimal adsorbent for separating CH4/N2 at the low pressure condition. From the simulated dynamic experiments, the ion-exchanged clinoptilolite using 0.2 mol/L NaCl solutions exhibits the best performance at 298 K under 0.2 MPa within 28 min, in relation with the raw clinoptilolite and other modified clinoptilolites, as a potential sorbent in kinetic PSA processes for the N2/CH4 separation. In the next work, CH4 separation in real coal mine gas would be researched using the clinoptilolite.